Corporate Social Responsibility Performance of Oil Multinationals in the Niger Delta: A Revisit from the Eyes of Host Communities - Akpor-Robaro , Masoje O.M.; Egwu , Bridget U.; Sanni , Michael R.; Ojedele , Mofoluwaso; Adeyanju , David O.; Ololade , Babatunde; Eyeh , Stephen O.; Julius-Adeoye , Rantimi J.; Erigbe , Patience A.; Omojola , Sunday O.; Akinwunmi , Abiodun A. (Journal of Ecohumanism, 2024)
This paper examined CSR performance of oil companies from the perspective of host communities in the Niger Delta. A questionnaire instrument was employed to elicit the perceptions of host communities using 355 participants selected by random sampling from 48 communities across three states. The data were analyzed with descriptive method, Kendall’s W test and Mean Rank Statistics. The results showed a weighted mean score less than 3.0 performance score criterion for all specified CSR dimensions indicating a perception of poor performance in each dimension. The mean of the mean scores was also less than 3.0, indicating a perception of poor overall performance. The Kendall’s W was 0.831; X2 was 507.037 at p=.000, indicating a high level of concordance between the respondents from the communities in their perception about CSR performance by oil companies. The results indicated high level of dissatisfaction by host communities about the CSR performance of oil companies.